(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of study is to compare advantages and disadvantages between two methods of extraperitoneal space creation for laparoscopic TEP repair of inguinal hernia. Methods: The Prospective interventional study was conducted from October 2018 to November 2019at SSG Hospital, Vadodara. A total 50 patients of inguinal hernia taken for laparoscopic TEP repair, among them patients were divided in two groups by envelope method of randomization. Extraperitoneal space created by Conventional Balloon Device method.Extraperitoneal space created by direct method(dissection). Results: In direct method group in 3 case Laparoscopic TEP converted to open hernioplasty due to poor visibility. In balloon method group no Laparoscopic TEP case converted to open. Conclusion: As there is no significant difference in intraoperative and post operative complications between direct method and balloon method for extraperitoneal space creation in laparoscopic TEP repair of inguinal hernia, both methods are safe and equally effective.